Dinamika Layanan Bimbingan dan Konseling dalam Mengatasi Permasalahan Siswa Sekolah Dasar - Jenal Maulana; Nunung Nadila; Ridwan Ridwan; Wulansari Wulansari; Vany Dwi Putri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The observation of guidance and counseling activities was conducted at SDN 2 Pasaleman, located in Pasaleman Village, Kresna Street, Dusun Pon. This study aimed to identify the problems faced by students and to examine the role of teachers in implementing guidance and counseling services at the elementary school level. Data were collected through direct observation in the school environment and interviews with homeroom teachers. The results indicated several student-related issues, including verbal bullying such as teasing, low learning motivation, fighting behavior among lower-grade students, and a tendency to skip school among upper-grade students. These issues were influenced by peer environments, limited supervision, and low awareness of the importance of education. Teachers have made various efforts, including providing guidance, applying individual approaches, and maintaining communication with parents. Additionally, character values are integrated into daily learning activities. In general, guidance and counseling services have been implemented, but further improvement in more systematic strategies and broader support is still required.